Impact of Social Networking on Political Processes: Exploring the Impact of Social Media on Political Processes (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The media assumes a crucial job in a democracy educating general society about political issues and going about as a guard dog against misuse of power. Amid race crusades the media gives information and investigation about the political gatherings' projects, arrangements, candidates and execution. Electronic communication appears to influence politicians to appear to be more remote there is still no association between politics where power is facilitated, and the network society itself. Likewise, social media has additionally changed politics in India. Its impact has affected the manner in which competitor campaign for their decision. Social media permits politicians and political parties a strategy to associate straightforwardly with people the nation over at a lessened expense and more noteworthy reach than conventional media. Social media isn't just the following in a line of communications technologies it has additionally changed regular exercises and associated people in a way at no other time conceivable. The paper means to look at the degree utilization of social media by the political parties to advance their image and political messages, among their supporters and peoples in social media. The paper expects to look at how social media impacts the political issues or political discourse